Medicinal plants used to treat human ailments in Wadla District, Northern Ethiopia: An ethnobotanical approach - Sara Yosef; Ermias Lulekal; Asfaw Debela; Muhidin Tahir (Elsevier, 2025)
Introduction: The global population started using traditional medicine before the advent of allopathic or modern medicine to manage several diseases. Nearly 887 plant species have been documented to heal different health problems. Documenting the traditional use of medicinal plants is a vital step in obtaining information on bioactive chemicals, preserving indigenous knowledge and ultimately interesting, medicinal plant species. This study aimed to document medicinal plants and the associated indigenous knowledge used to treat human ailments. Methods: The data were collected using a combination of sampling techniques, including strict random sampling, stratified random sampling, (for general informants) and snowball sampling, purposive and random sampling (for key informants). Semistructured interviews, group discussions, guided field walks, and field observations were used to collect the data. We analysed the data using descriptive statistics, including direct matrix rankings, preference rankings, informant consensus factors, and fidelity levels. Results: A total of 200 informants (68 % males and 32 % females) living in 10 kebeles were selected. A total of 107 plant species belonging to 51 families and 71 genera were identified by local people to address human ailments. The Solanaceae family represented the greatest number of species (7 species). Leaves were the most dominant plant parts used for remedy preparation (47 %). The most common routes of administration were oral (47 %). The categories with the highest ICF values were diseases of the nervous system (0.96). Datura stramonium was the most preferred species for treating wounds. The highest fidelity level (93.3 %) was recorded for Guizotia abyssinica. Eucalyptus globulus was ranked first in a direct matrix ranking exercise of multipurpose medicinal plants. Conclusion: This study revealed that the study area has a considerable number of traditional medicinal plants that are used to address a wide range of health problems. Although community members rely on medicinal plant species to manage various health problems, they threaten medicinal plants in the country, and indigenous knowledge is rapidly vanishing from communities; thus, conservation measures should be taken to protect these plants in their natural sites, agricultural areas and villages.